Electrodes with lithium-rich nickel manganese oxides

By using lithium-rich nickel-manganese oxide active materials, conductive component mixtures and acid functional group binder systems in the cathode of lithium-ion batteries, the problem of degradation of lithium-ion batteries after circulation is solved, and high cycle stability and low cycle stability are achieved The effect of voltage attenuation.

CN119495705APending Publication Date: 2025-02-21GM GLOBAL TECHNOLOGY OPERATIONS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311467034.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-17
Filing Date
2023-11-06
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The performance of lithium-ion batteries is degraded after charging and discharging cycles, especially the requirements of high operating voltage and high reversible capacity are difficult to meet, and there are problems of cycling stability and voltage attenuation.

Method used

Lithium-rich nickel-manganese oxide is used as the active material, and a mixture of conductive elements with low aspect ratio, plate-shaped and needle-shaped, and a binder system containing acid functional groups is formed to form an efficient cathode material.

Benefits of technology

It significantly improves the cycle stability and discharge retention rate of lithium-ion batteries, reduces voltage attenuation, and meets the needs of high operating voltage and high reversible capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495705A_ABST
    Figure CN119495705A_ABST
Patent Text Reader

Abstract

A cathode for a lithium ion battery includes an active material present in an amount of 70 to 99 wt%, wherein the active material includes a lithium-rich nickel manganese oxide; a conductive network of a mixture of conductive elements present in an amount of 0.25 to 20 wt%, wherein the mixture of conductive elements comprises two or more of low aspect ratio particles, plate-like particles, and needle-like particles; and a binder system present in an amount of 0.25 to 10 wt%, where the binder system comprises a primary binder polymer and an acid group or salt thereof, where the amount is based on the total weight of the cathode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The subject disclosure relates to electrodes for lithium-ion batteries and batteries having such electrodes. Background Art

[0002] Advanced energy storage devices and systems are needed to meet the energy and / or power requirements of various products, including automotive products, such as start-stop systems (e.g., 12V start-stop systems), battery auxiliary systems, hybrid electric vehicles ("HEV"), and electric vehicles ("EV"). A typical lithium-ion battery includes at least two electrodes and an electrolyte and / or a separator. One of the two electrodes serves as a cathode and the other electrode serves as an anode. The separator and / or electrolyte may be disposed between the negative electrode and the cathode. The electrolyte is suitable for conducting lithium ions between the electrodes and, like the two electrodes, may be in solid and / or liquid form and / or a mixture thereof. In the case of a solid-state battery comprising solid electrodes and a solid electrolyte, the solid electrolyte may physically separate the electrodes so that different separators are not required.

[0003] Conventional rechargeable lithium-ion batteries operate by reversibly transferring lithium ions back and forth between an anode and a cathode. For example, lithium ions may move from the cathode to the anode during battery charging, and move in the opposite direction when the battery is discharged. Such lithium-ion batteries may reversibly supply power to an associated load device as needed. More specifically, power may be supplied to the load device by the lithium-ion battery until the lithium content of the anode is effectively depleted. The battery may then be recharged by passing a suitable direct current in the opposite direction between the electrodes.

[0004] The performance of lithium-ion batteries may degrade after charge and discharge cycles. For example, capacity loss may occur after cycling.

[0005] It is desirable to have a battery that has a high operating voltage and a high reversible capacity while having good cycling stability and reduced voltage fade. Summary of the invention

[0006] In one exemplary embodiment, a cathode for a lithium ion battery is disclosed, wherein the cathode comprises an active material present in an amount of 70 to 99 wt %, wherein the active material comprises a lithium-rich nickel manganese oxide; a conductive network of a mixture of conductive elements present in an amount of 0.25 to 20 wt %, wherein the mixture of conductive elements comprises two or more of low aspect ratio particles, plate-like particles, and needle-like particles, and a binder system present in an amount of 0.25 to 10 wt %, wherein the binder system comprises a primary binder polymer and an acid group or a salt thereof. The amount is based on the total weight of the cathode.

[0007] In addition, the cathode may include one or more of the features described herein. The lithium-rich nickel manganese oxide may have the formula xLi2MnO3*(1-x)LiMO2; where 0 < x ≤ 0.5, M includes Ni, Mn, and optionally Co, and the molar ratio of Ni:Mn is in the range of 1:4 to 1:1.

[0008] The mixture of conductive elements may include low aspect ratio particles in an amount of 0.1 to 10 wt% based on the total weight of the cathode, plate-like particles in an amount of 0 to 10 wt%, and needle-like particles in an amount of 0.05 to 5 wt% based on the total weight of the cathode.

[0009] The cathode may contain 90 to 99 wt% of the lithium-rich nickel manganese oxide based on the total weight of the cathode.

[0010] The low aspect ratio particles may be carbon black, the plate-like particles may be graphene nanosheets, and the needle-like particles may be carbon nanotubes.

[0011] The low aspect ratio particles may have an average particle size of 2 nm to 200 nm and an aspect ratio of 2:1 to 1:1.

[0012] The plate-like particles may have a thickness in the range of 5 nm to 100 nm and a dimension orthogonal to the thickness in the range of 1 to 25 µm.

[0013] The needle-like particles may have a length of 0.1 to 100 µm and an aspect ratio of 10 to 5000.

[0014] The active material may also contain up to 60 wt% of one or more additional metal oxides or phosphates. The additional metal oxides or phosphates may include lithium manganese oxide (Li (1+x) Mn2O4, where 0.1 ≤ x ≤ 1) (LMO), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) (LNMO), lithium cobalt oxide (LiCoO2) (LCO), lithium nickel manganese cobalt oxide (LiNi 1-x- y Co x Mn y O2) (where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1) (NMC), lithium cobalt manganese aluminum oxide (LiNi 1-x-y-z Co x Mn y Al z O2, where 0.0 < x + y + z < 0.25) (NCMA), lithium iron phosphate (LiFePO4), lithium vanadium phosphate (LiVPO4), lithium manganese iron phosphate (LiMn 1-x Fe x PO4, where 0 ≤ x ≤ 1) or a combination thereof.

[0015] Part of the conductive elements can be functionalized with hydroxyl or carboxyl groups.

[0016] The main binder polymer can include polyvinylidene fluoride.

[0017] The acid group can be a carboxylic acid or a sulfonic acid.

[0018] The acid group can be present in an amount of 0.05 to 10 milliequivalents per gram of the binder system.

[0019] The acid group can be provided on an acid-functional polymer different from the main binder polymer.

[0020] The acid group can be present in an amount of 0.05 to 10 milliequivalents per gram of the acid-functional polymer.

[0021] Based on the total weight of the binder system, the binder system can comprise 50 to 95 wt% of the main binder polymer and 5 to 50 wt% of the acid-functional polymer.

[0022] The acid-functional polymer can include acid-functionalized polyvinylidene fluoride, (co)polymers or aromatic ionomers, sulfonated phenylated polyphenylene, sulfonated derivatives of poly(arylene ether), poly(arylene ether sulfone), poly(arylene sulfide), sulfonated polyimide, sulfonated polyphenylene, or combinations thereof.

[0023] In a specific embodiment, the cathode comprises 90 to 99 wt% of lithium-rich nickel manganese oxide having the formula Li[Li 1 / 3-2x / 3 Ni x M n2 / 3-x / 3 O2, where 0 < x < 0.5, 0.5 to 5 wt% of the main binder polymer, 0.1 to 1 wt% of the acid-functional polymer, 0.05 to 1 wt% of carbon nanotubes, 0.1 to 5 wt% of carbon black, and 0 to 3 wt% of graphene nanosheets, where wt% is based on the total weight of the cathode.

[0024] In another exemplary embodiment, an electrochemical cell unit is disclosed, which includes an anode disposed on a current collector, a cathode disposed on the anode current collector, and an electrolyte, wherein the cathode includes an active material present in an amount of 70 to 99 wt%, wherein the active material includes lithium-rich nickel manganese oxide; a conductive network of a mixture of conductive elements present in an amount of 0.25 to 20 wt%, wherein the mixture of conductive elements comprises two or more of low aspect ratio particles, plate-like particles, and needle-like particles, and a binder system present in an amount of 0.25 to 10 wt%, wherein the binder system comprises a main binder polymer and an acid group or its salt. The cathode in the electrochemical cell unit can include one or more additional features as described herein.

[0025] The above features and advantages and other features and advantages of the present disclosure are apparent from the following detailed description when taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Other features, advantages and details appear, by way of example only, in the following detailed description, which refers to the accompanying drawings, in which:

[0027] Figure 1 is a schematic side cross-sectional view of a cathode;

[0028] Figure 2 Is has Figure 1 A schematic side cross-sectional view of an electrochemical cell of a battery having a cathode of ;

[0029] Figure 3A is a graph of capacity versus cycle for the cathode formulation described in Example 1;

[0030] Figure 3B is a graph of discharge retention versus cycles for the cathode formulation described in Example 1;

[0031] Figure 4 is a graph of voltage versus capacity for cells having comparative cathode formulations;

[0032] Figure 5 is a graph of voltage versus capacity for a battery having a cathode formulation according to an example;

[0033] Fig. 6A is a graph of capacity versus cycles for the cathode formulation described in Example 3; and

[0034] Figure 6B is a graph of discharge retention versus cycles for the cathode formulation described in Example 3. DETAILED DESCRIPTION

[0035] Lithium-rich active materials (LMRs) for cathodes can provide high average operating voltages and high capacities, but the practical implementation of these is challenging. One challenge is poor cycling stability (e.g., voltage decay and capacity decay during cycling). Various approaches have been proposed to address these challenges, including surface modification of LMRs with metal oxides, doping of LMRs, annealing of LMRs, and managing morphology or structure. These complex approaches focus primarily on the LMRs themselves. It has been surprisingly discovered that the selection of formulations for the cathode's active materials, binders, and conductive elements can be a simple and cost-effective approach to achieving the benefits of using LMR materials while significantly improving cycling stability (e.g., reducing voltage decay and / or capacity decay).

[0036] The following description is merely exemplary in nature and is not intended to limit the present disclosure, its application, or uses. It should be understood that throughout the drawings, corresponding reference numerals indicate like or corresponding parts and features.

[0037] As disclosed herein, the cathode includes a lithium-rich nickel manganese oxide active material, a mixture of conductive elements of different geometries forming a conductive network, and a binder system including acid functional groups.

[0038] Active Materials

[0039] The active material includes lithium-rich nickel manganese oxide. Lithium-rich means that the molar ratio of lithium to other metals (such as nickel, manganese, and optionally additional transition metals such as Co) in the active material is greater than 1:1, for example, 1.1:1 to 1.49:1. For example, the lithium-rich nickel manganese oxide can be represented as xLi2MnO3*(1-x)LiMO2; 0 < x ≤ 0.5, where M includes Ni and Mn, and the molar ratio of Ni:Mn is in the range of 1:4 to 1:1. In one example, M consists of or consists essentially of Ni and Mn. In another example, M further includes additional transition metals, such as Co. In the presence of such additional transition metals (e.g., Co), the ratio of additional transition metal:Mn can be less than 1:5 or less than 1:10. As another example, the lithium-rich metal oxide can be represented by the formula Li[Li 1 / 3-2y / 3 Ni y Mn 2 / 3-y / 3 O2, where 0 < y < 0.5.

[0040] The active material can be in the form of particles with an average particle size of 0.5 to 30 or to 20 micrometers (i.e., μm or micrometers). The particle size can be measured, for example, by light scattering of a solvent dispersion using low-angle laser light scattering (LALLS) or by electron microscopy of dry powders or coatings.

[0041] Optionally, in addition to the lithium-rich nickel manganese oxide, the active material can contain one or more additional metal oxides or phosphates, such as lithium manganese oxide (Li (1+x) Mn2O4, where 0.1 ≤ x ≤ 1) (LMO), lithium nickel manganese oxide (LiN i0.5 M n1.5 O4) (LNMO), lithium cobalt oxide (LiCoO2) (LCO), lithium nickel manganese cobalt oxide (LiNi 1-x-y Co x Mn y O2) (where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1) (NMC), lithium cobalt manganese aluminum oxide (LiNi 1-x-y-z Co x Mn y Alz O2, where 0.0 < x + y + z < 0.25) (NCMA), lithium iron phosphate (LiFePO4), lithium vanadium phosphate (LiVPO4), lithium manganese iron phosphate (LiMn 1-x Fe x PO4, where 0 ≤ x ≤ 1), and combinations thereof. Based on the total weight of the active material, the amount of such additional metal oxide can be from 0, 0.5, 1, 2, 3, 5, 5 up to 60, up to 50, up to 40, up to 30, up to 20 or up to 10 wt%. The active material can be cobalt-free.

[0042] Based on the total weight of the cathode, the content of the active material in the cathode can be from 50, 60, 70, 80, 85, 90, 92 or 95 up to 99 or up to 98 wt%.

[0043] Conductive components

[0044] The conductive element includes small particles of various geometries. In particular, the conductive element includes particles of two or more of the following: small particles with a low aspect ratio, platelet-shaped particles, and needle-shaped particles. For example, the conductive element is a binary mixture of small particles with a low aspect ratio and needle-shaped particles. In another example, the conductive element is a binary mixture of small particles with a low aspect ratio and platelet-shaped particles. In yet another example, the conductive element is a binary mixture of platelet-shaped particles and needle-shaped particles. In another example, the conductive particles can be a ternary mixture of small particles with a low aspect ratio, platelet-shaped particles, and needle-shaped particles.

[0045] The small particles with a low aspect ratio can be substantially spherical or can be irregular, where the aspect ratio of the longest dimension to the shortest dimension is 2:1 to 1:1, 1.5:1 to 1:1, or 1.2:1 to 1:1. For example, the small particles with a low aspect ratio can be carbon black. The low aspect ratio particles, such as carbon black, can have an average particle diameter of 2 nanometers up to 200, up to 150 or up to 200 nanometers. The particle size can be measured, for example, by low angle laser light scattering (LALLS). The low aspect ratio particles can have a surface area in the range of 10 to 500 square meters per gram (m 2 / g) and a conductivity in the range of 0.5 S / cm to 50 S / cm. In various embodiments, the carbon black can be furnace black with a surface area of about 45 - 65 m 2 / g. Alternatively, in various embodiments, the carbon black can be, for example, acetylene black with a surface area of about 130 - 240 m 2 / g. Alternatively, in various embodiments, the carbon black can be, for example, another acetylene black with a surface area of about 280 m 2 / g to 320 m 2 / g.

[0046] Surface area can be measured, for example, by the Brunauer-Emmett-Teller (BET) method.

[0047] Conductivity can be measured, for example, by a 4-point probe measurement or by using a potentiostat to place various currents (I) in amperes [A] into the electrodes and measure the corresponding voltage [V]. Using Ohm's law, V = I*R, the resistance (R) in ohms [Ω] can be calculated (R = V / I).

[0048] The plate-like particles can have a thickness of about 5 nanometers to 100 nanometers and a dimension orthogonal to the thickness of about 1 to 25 microns. For example, the plate-like structure can be a graphene sheet or a graphene sheet stack, and the graphene sheet stack has at least two graphene sheets stacked on top of one another. Each graphene sheet is formed by a single layer of carbon atoms arranged in a honeycomb lattice. The graphene sheet stack can be in the form of a graphene sheet, and can include one stacked on top of another greater than 10 graphene sheets or greater than 20 graphene sheets and up to 50 graphene sheets. Alternatively, the graphene sheet stack can be in the form of a graphene nanosheet, which has a disc-like or lens-like shape and is composed of a stack of 2 to 10 graphene sheets. The plate-like structure, such as a graphene nanosheet, can have an aspect ratio greater than or equal to about 20, or an aspect ratio greater than or equal to about 100 to 1000. The plate-like structure, such as a graphene nanosheet, may have a dimension orthogonal to the thickness (e.g., diameter) of 1-25, or 2-10 microns and a thickness of 5 nanometers to 100 nanometers. The plate-like structure, such as a graphene nanosheet, may have a porosity of about 90%. The plate-like structure, such as a graphene nanosheet, may have a porosity of 10 nanometers to 100 nanometers. 2 / g-200m 2 The plate-like structure, such as a graphene nanosheet, may have an electrical conductivity of about 100 Siemens / cm (S / cm) measured in a direction perpendicular to its major surface and about 10 S / cm measured in a direction parallel to its major surface. 7 The conductivity is S / cm.

[0049] Porosity can be measured, for example, by mercury intrusion porosimetry. Surface area can be measured, for example, by low angle laser light scattering.

[0050] Needle-like structures (e.g., having an aspect ratio (length: diameter or length: width) of greater than or equal to about 10, greater than or equal to 50, greater than or equal to 100, or greater than or equal to about 500, greater than or equal to about 1000, and up to 5000, or up to 3000). For example, the needle-like conductive particles may include carbon nanotubes. Needle-like conductive particles, such as carbon nanotubes, can have a substantially cylindrical cross-section in a direction orthogonal to the longest dimension (length). Needle-like conductive particles (such as carbon nanotubes) can have an aspect ratio (length: diameter (or length: width if not cylindrical)) of greater than or equal to about 10, greater than or equal to 50, greater than or equal to 100, or greater than or equal to about 500, greater than or equal to about 1000, and up to 5000, or up to 3000. Needle-shaped conductive particles (such as carbon nanotubes) can have a dimension orthogonal to length (e.g., diameter) in the range of 0.5 nanometers to 50 nanometers, and a length in the range of from 0.1 micrometers, from 0.5 micrometers, from 1 micrometer, from 2 micrometers, or from 3 micrometers up to 100 micrometers, up to 50 micrometers, up to 20 micrometers, or up to 10 micrometers.

[0051] The needle-shaped conductive particles, such as carbon nanotubes, can have a porosity greater than about 97%. The needle-shaped conductive particles can be in the form of single-walled carbon nanotubes (SWCNTs) and / or multi-walled carbon nanotubes (MWCNTs). The surface area of ​​the needle-shaped conductive particles (such as carbon nanotubes) can be from 50 m 2 / g、100m 2 / g, 200m 2 / g、300m 2 / g or 400m 2 / g until 1300m 2 / g, up to 1000m 2 / g, up to 700m 2 / g or up to 500m 2 / g, and the conductivity is in the range of from 102S / cm to 106S / cm. More specifically, the MWCNT may have, for example, 260 to 350m 2 / g or 280 to 320m 2 / g surface area. SWCNTs can have, for example, 380 m 2 / g to 420m 2 / g surface area. Bundling of carbon nanotubes can reduce the measured surface area.

[0052] Optionally, a portion of the conductive elements, eg, carbon nanotubes, may include one or more hydroxyl (-OH) functional groups and / or carboxyl (-COOH) functional groups, which may help to evenly disperse the carbon nanotubes throughout the thickness of the cathode.

[0053] Based on the gross weight of the cathode, the total amount of the conductive elements in the cathode can be from 0.25 wt %, or 0.5 wt %, or 1 wt % up to 49.8 wt %, up to 25 wt %, up to 20 wt %, up to 10 wt %, or up to 5 wt %. Based on the gross weight of the cathode, low aspect ratio particles (such as carbon black) can be present in an amount of, for example, from 0.1 or 0.25 wt % up to 10 wt %, up to 5 wt %, up to 3 wt % or up to 2 wt %. Based on the gross weight of the cathode, plate-like conductive particles such as graphene sheet stacks can be present in an amount of from 0 wt %, or 0.1 wt %, or 0.25 wt %, up to 10 wt %, up to 5 wt %, up to 3 wt % or up to 2 wt %. Based on the gross weight of the cathode, needle-shaped conductive particles (such as carbon nanotubes) can be present in an amount of from 0 wt %, or 0.05 wt %, up to 5 wt %, or up to 3 wt %, or up to 1 wt %.

[0054] As a specific example, the conductive element can be 0.7 to 1 wt% carbon black and 0.5 to 0.7 wt% graphene nanosheets, and 0.05 to 0.15 wt% single-walled carbon nanotubes (SWCNTs) can be used in a ternary mixture based on the total weight of the cathode. As another specific example, the conductive element can be 0.25-1.5% multi-walled carbon nanotubes (MWCNTs) and 1.25-0% carbon black, respectively, which can be used in a binary mixture.

[0055] Binder system

[0056] The cathode includes a binder system. The binder system includes a primary polymer binder. For example, the primary polymer binder may include a primary polymer binder, such as a polyvinylidene fluoride (PVDF) homopolymer or copolymer. The binder system includes an acid functional group or a salt thereof. The acid functional group may contribute to the dispersion of other components of the cathode. Examples of acid functional groups or their salts include carboxylic acid groups, sulfonic acid groups and their salts. The acid functionality may be present in the binder system in an amount of 0.0025 to 3 milliequivalents (meq) / gram of binder system. The acid functionality may be provided by an acid functional polymer different from the primary polymer binder. For example, based on the gross weight of the binder system, the binder system may include 50 to 95, or 70 to 90 weight % of the primary binder polymer and from 5 to 50, or 10 to 30 weight % of the acid functional polymer. The amount of acid functionality on the acid functional polymer may be from 0.05 to 5 milliequivalents / gram of acid functional polymer. The acid-functional polymer may include an acid-functionalized PVDF homopolymer or copolymer, a sulfonated phenylated polyphenylene (SPPP-H) and a sulfonated derivative of a poly(arylene ether) (SPAE), a poly(arylene ether sulfone) (SPAES), a poly(arylene sulfide) (SPAS), a sulfonated polyimide (SPI), a sulfonated polyphenylene (SPP), or a combination of two or more thereof. The acid-functionalized PVDF (co)polymer may be, for example, P(VDF (vinylidene fluoride): TFE (tetrafluoroethylene): 4:1 w / w).

[0057] For example, the polymer binder system may include 95-50% polyvinylidene fluoride (PVDF) homopolymer and 5-50% acid functionalized PVDF (co)polymer or aromatic ionomer. The acid functionalized PVDF (co)polymer may be, for example, P(VDF (vinylidene fluoride): TFE (tetrafluoroethylene):: 4: 1 w / w) having approximately 0.10 to 0.15 meq carboxylic acid / gram polymer.

[0058] As another example, the acid functionalized polymer can have different backbone compositions and acid loadings, such as sulfophenylated polyphenylene (SPPP-H) having about 3 to 3.5 meq sulfonic acid per gram of polymer.

[0059] The acid functionalized polymer may have, for example, a meq of about 0.05 to 10.0 per gram of polymer.

[0060] The acid-functionalized polymer may be, for example, one of sulfonated phenylated polyphenylene (SPPP-H) and sulfonated derivatives of poly(arylene ether) (SPAE), poly(arylene ether sulfone) (SPAS), poly(arylene sulfide) (SPAS), sulfonated polyimide (SPI), sulfonated polyphenylene (SPP), and combinations thereof, and one or more cations selected from H+, Li+, Na+, K+, and NH4+.

[0061] Based on the total weight of the cathode, the binder system is present in the cathode in an amount from 0.25 wt%, 0.5 wt% or 1 wt% up to 45 wt%, up to 20 wt%, up to 10 wt% or up to 5 wt%.

[0062] In one specific example, the cathode can have 90 to 99 wt% of a lithium-rich nickel manganese oxide (which has the formula Li[Li 1 / 3-2x / 3 Ni x Mn 2 / 3-x / 3 O2, where 0 < x < 0.5), 0.5 to 5% of a primary binder polymer, 0.1 to 1% of an acid-functional polymer, 0.05 to 1% of single-walled carbon nanotubes, 0.1 to 3% of carbon black, and 0.1 to 2 wt% of graphene nanosheets, where the percentages are based on the total weight of the cathode.

[0063] In another specific example, the cathode has from 90 to 99 wt% of a lithium-rich nickel manganese oxide, which has the formula Li[Li 1 / 3-2x / 3 Ni x Mn 2 / 3-x / 3 O2, where 0 < x < 0.5, 0.5 to 5% of a primary binder polymer, 0.1 to 1% of an acid-functional polymer, 0.05 to 1.5% of multi-walled carbon nanotubes, and 0.1 to 3% of carbon black, where the percentages are based on the total weight of the cathode.

[0064] Cathode and method of forming a cathode

[0065] The cathode can be formed by combining an active material, a conductive material, and a binder system in a solvent and coating the mixture onto a substrate. The substrate can be the current collector of the cathode. The coated layer is dried to form the cathode. For example, the conductive material can be combined with a solvent such as N-methylpyrrolidone (NMP) and stirred for a time such as 5 to 15 minutes. Then the binder system can be added with stirring for an additional 2 to 10 minutes. Then the cathode active material can be added with stirring for an additional 2 to 10 minutes. Additional solvent can be added with subsequent stirring to obtain a slurry having a viscosity suitable for coating. The slurry can be coated on the substrate (e.g., the current collector) and then dried. The drying can be carried out in an oven at, for example, 50 to 120 °C and / or under vacuum.

[0066] According to an exemplary embodiment, as Figure 1As shown, the cathode 12 includes a composite of active material particles 32, a binder 34, a dispersant (not shown), and a combination of conductive additive types (36, 38, 40). In assembly, the cathode 12 is disposed on the major surface 20 of the current collector 22 in the form of a continuous uniform layer of material. The cathode 12 may include open pores 44 defined by the porous structure of the cathode 12, which may be infiltrated with the electrolyte 18. The cathode 12 may have a thickness measured from the major surface 20 of the cathode current collector 22 to its facing surface 42, which is in the range of 5 microns to 600 microns. The combination of active material particles 32, binder 34, dispersant, and conductive carbon additive types is substantially uniformly distributed throughout the cathode 12 on the major surface 20 of the cathode current collector 22.

[0067] Electrochemical battery cell

[0068] The cathode can be used in an electrochemical cell comprising a cathode, an anode and an electrolyte. Figure 2 As shown, the electrochemical cell 10 may include a cathode 12, an anode 14 spaced apart from the cathode 12, and a porous separator 16 located between the cathode 12 and the anode 14. The cathode 12 and the anode 14 and the porous separator 16 are permeated with an electrolyte 18, which provides a medium for the lithium ions to be conducted therethrough. The cathode 12 is disposed on a major surface 20 of a cathode current collector 22, and the anode 14 is disposed on a major surface 24 of an anode current collector 26. In practice, the cathode current collector 22 and the anode current collector 26 may be electrically coupled to a power source or load 28 via an external circuit 30. The electrochemical cell 10 may be combined with one or more additional electrochemical cells to form a lithium ion battery.

[0069] Anode 14 includes active material. The active material can be, for example, graphite, a silicon-based graphite blend or silicon-based particles. Anode 14 can also include a binder. The binder can be the same or different from the binder used for the cathode. The binder can include, for example, PVDF, polyacrylonitrile (PAN), guar gum (GG), gum arabic (GA), polysaccharide lambda carrageenan (CGN), cellulose polymers such as carboxymethyl cellulose (CMC), sodium alginate (SA), polyimide (PI), polyvinyl alcohol (PVA), chitosan (CS), styrene butadiene rubber (SBR), polyacrylic acid (PAA) or amino polyacrylic acid PAA-NH3.

[0070] Anode 14 may include a conductive element such as carbon black, graphene, carbon nanotubes, or a combination thereof.

[0071] The separator 16 may include, for example, a polymer film, such as a polypropylene film or a coated polypropylene film.

[0072] Electrolyte 18 may include, for example, a metal salt dissolved in a solvent, such as a lithium salt, optionally with additional electrolyte additives. For example, the lithium salt may include lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl) imide (LiFSI) or lithium bis(trifluoromethanesulfonyl) imide (LiTFSI). The molar concentration may be 0.5 to 2 moles. The solvent may include, for example, ethyl methyl carbonate (EMC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), diethyl carbonate (DEC), dimethyl carbonate (DMC), propylene carbonate (PC), polyethylene carbonate (PEC), ethylene carbonate (VC), trimethyl phosphate (TMP), sulfolane (SL), difluorobenzene (DFC) or a combination thereof. The electrolyte additive may include, for example, VC, lithium difluoro(oxalato)borate (LiDFOB), lithium difluorophosphate (LiDFP), FEC, lithium bis(oxalato)borate (LiBOB), prop-1-ene-1,3-sulfone (PES), ethylene sulfite (ES), succinonitrile (SCN), TMP or tris(trimethylsilyl)phosphite (TMPi), or a combination thereof.

[0073] Example

[0074] Example 1

[0075] The method comprises combining and mixing a prepolymer having the formula Li[Li 1 / 3-2x / 3 Ni x Mn 2 / 3-x / 3 ]O2-rich lithium (LMR) active particles (where 0.3≤x≤0.4PVDF), as carbon black with 65m 2 / g surface area of ​​furnace black, with 65m 2 / g surface area of ​​graphene nanosheets, with 400m 2 The formulation was prepared by using single-walled carbon nanotubes with a surface area of ​​1.17 W / g and an acid-functional polymer having a sulfonated phenylated polyphenylene (sPPP) backbone.

[0076] The specific recipe prepared is shown in Table 1. The conductive additive was first combined with NMP and milled for 10 minutes. The binder and dispersant polymers were added and mixed for another 5 minutes. The LMR particles were then added and mixed for another 5 minutes. Additional solvent was added and mixed for 10 minutes. The mixture was applied to the current collector and dried.

[0077] Electrochemical cells were prepared including cathodes of these formulations 1-3 and anodes (having a mixture of silica-graphite active particles, a conductive element, and a water-based binder), polypropylene separators, and a high voltage stable LiPF6-based electrolyte (Electrolyte A). These cells were charged to 4.6 V and discharged to 2 volts at a constant voltage, twice the C / 3 (C rate) (for a full capacity battery, charging or discharging in 3 hours). The C rate is a measure of the current with which a battery is charged and discharged.

[0078] The battery cell was then discharged to 2 volts at a C rate of C / 3, and the specific discharge capacity and discharge capacity retention rate in milliamperes per gram [mAh / g] were evaluated. The discharge capacity retention rate was calculated by dividing each specific discharge capacity by the highest discharge capacity in the entire cycle, cycled and evaluated for capacity and discharge retention rate. Figure 3A The specific capacity is shown on the y-axis in milliampere hours per gram mass (mAh / g), and the cycle number is shown on the x-axis. Figure 3B The discharge retention rate (%) is shown on the y-axis, and the number of cycles is shown on the x-axis. Formulation 1 is represented by triangles, Formulation 2 is represented by circles, and Formulation 3 is represented by stars. Comparative Formulation 1 containing only carbon black as a conductive additive shows a faster decline in capacity and discharge retention rate compared to the composition having a mixture of conductive carbon as a conductive additive.

[0079] Table 1

[0080]

[0081] Example 2

[0082] The electrochemical cells prepared using Formulations 1 and 2 as disclosed in Example 1 were evaluated for voltage decay during discharge. Figure 4 and Figure 5 In FIG. 1 , the y-axis is voltage (V) and the x-axis is capacity in milliampere hours per gram mass (mAh / g). The voltage curves for Formulation 1 are shown in FIG. 1 for cycle 1 (squares), cycle 2 (circles), and cycle 3 (triangles). Figure 4 The voltage curve of formula 1 is shown in Figure 5 In which loop 1 is represented by a square symbol, loop 3 is represented by an inverted triangle symbol, loop 200 is represented by a star symbol, and loop 400 is represented by a diamond symbol. Figure 4 and 5 As shown, Formulation 2 shows significantly better cycling stability than Comparative Formulation 1.

[0083] Example 3

[0084] Electrochemical cells were prepared as disclosed in Example 1 using Formulation 2 (1.2 wt% PVDF and 0.3 wt% acid functionalized polymer) and Comparative Formulation 4 having 1.5% PVDF but no dispersed polymer. Fig. 6A The specific capacity is shown on the y-axis in milliampere hours per gram mass (mAh / g) and the number of cycles is shown on the x-axis. Figure 6B The discharge retention ratio (%) on the y-axis and the number of cycles on the x-axis are shown. Formulation 2 is represented by solid circles, while comparative formulation 4 is represented by hollow circles. Both formulations contain 0.1 wt% single-walled carbon nanotubes, 0.8 wt% furnace black, and 0.6 wt% graphene nanoparticles. Fig. 6A and 6B As shown, including a dispersed polymer in the binder system improves the cycle life performance.

[0085] Example 4

[0086] Electrochemical cells were prepared as disclosed in Example 1 using Formulation 3, Formulation 5 did not include graphene, Formulation 6 omitted graphene, used different carbon blacks and used acetylene carbon black from Denka and multi-walled carbon nanotubes from Cabot. The amounts are shown in Table 2. The cells used different electrolytes B. Each formulation showed a discharge retention of more than 97% at 100 cycles.

[0087]

[0088] The terms "a" and "an" do not indicate a limitation of quantity, but rather indicate the presence of at least one of the referenced item. Unless the context clearly indicates otherwise, the term "or" means "and / or". References to "aspects" throughout the specification mean that a particular element (e.g., a feature, structure, step, or characteristic) described in conjunction with that aspect is included in at least one aspect described herein, and may or may not be present in other aspects. In addition, it should be understood that the described elements may be combined in any suitable manner in the various aspects.

[0089] When an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.

[0090] Unless stated to the contrary herein, all test standards are the most current standards in effect as of the filing date of this application or, if priority is claimed, the filing date of the earliest priority application in which the test standards appear.

[0091] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.

[0092] Although the above disclosure has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made and equivalents may be substituted for its elements without departing from its scope. In addition, many modifications may be made to adapt specific circumstances or materials to the teachings of the disclosure without departing from the basic scope of the disclosure. Therefore, it is intended that the disclosure is not limited to the specific embodiments disclosed, but will include all embodiments falling within its scope.

Claims

1. A cathode for a lithium-ion battery, wherein the cathode comprises: an active material present in an amount from 70 to 99% by weight, wherein the active material comprises a lithium-rich nickel manganese oxide; a conductive network of a mixture of conductive elements present in an amount from 0.25 to 20% by weight, wherein the mixture of conductive elements comprises two or more of low aspect ratio particles, plate-like particles, and needle-like particles, and a binder system present in an amount from 0.25 to 10% by weight, wherein the binder system comprises a main binder polymer and an acid group or its salt, wherein the amounts are based on the total weight of the cathode.

2. The cathode according to claim 1, wherein the lithium-rich nickel manganese oxide has the formula xLi2MnO3*(1-x)LiMO2; where 0 < x ≤ 0.5, M comprises Ni, Mn, and optionally Co, and the molar ratio of Ni:Mn is in the range of 1:4 to 1:

1.

3. The cathode according to claim 1, wherein the mixture of conductive elements comprises low aspect ratio particles in an amount from 0.1 to 10% by weight based on the total weight of the cathode, plate-like particles in an amount from 0 to 10% by weight, and needle-like particles in an amount from 0.05 to 5% by weight, and wherein the low aspect ratio particles are carbon black, the plate-like particles are graphene nanosheets, and the needle-like particles are carbon nanotubes.

4. The cathode according to claim 1, wherein the active material further comprises up to 60% by weight of one or more additional metal oxides or phosphates.

5. The cathode according to claim 1, wherein the main binder polymer comprises polyvinylidene fluoride.

6. The cathode according to claim 1, wherein the acid group is present in an amount of 0.05 to 10 milliequivalents / gram of the binder system and is a carboxylic acid or a sulfonic acid.

7. The cathode according to claim 1, wherein the acid group is provided on an acid-functional polymer different from the main binder polymer, and the acid group is present in an amount of 0.05 to 10 milliequivalents / gram of the acid-functional polymer.

8. The cathode according to claim 7, wherein the binder system comprises from 50% to 95% by weight of the main binder polymer and from 5% to 50% by weight of the acid-functional polymer based on the total weight of the binder system.

9. The cathode according to claim 7, wherein the acid-functional polymer comprises an acid-functionalized polymer polyvinylidene fluoride, (co)polymer or aromatic ionomer, sulfonated phenylated polyphenylene, sulfonated derivative of poly(arylene ether), poly(arylene ether sulfone), poly(arylene sulfide), sulfonated polyimide, sulfonated polyphenylene, or a combination thereof.

10. An electrochemical cell unit, comprising a cathode disposed on a current collector, an anode disposed on an anode current collector, and an electrolyte, wherein the cathode comprises: an active material present in an amount from 70 to 99% by weight, wherein the active material comprises a lithium-rich nickel manganese oxide; A conductive network of a mixture of conductive elements present in an amount from 0.25 to 20 weight percent, wherein the mixture of conductive elements comprises two or more of low aspect ratio particles, plate-like particles, and needle-like particles, and a binder system present in an amount of from 0.25 to 10 wt %, wherein the binder system comprises a primary binder polymer and an acid group or a salt thereof, The amounts stated are based on the total weight of the cathode.